KMV model in predicting sovereign debt default / Siti Mahani Isman ... [et al.] - Isman, Siti Mahani; Mohd Ngasri, Nur Faiqah; Misman, Nazihah; Muhamad Yusof, Norliza (Universiti Teknologi MARA, Negeri Sembilan, 2022)
Extensive research recognized that Greece is one of the countries that faced sovereign debt default due to its bankruptcy in 2009 (Arghyrou & Tsoukalas, 2011). The failure of a government to manage well its sovereign debt in the earlier stage can harm a country. According to the Ministry of Finance Malaysia (2018), Malaysia's sovereign real debt and liabilities amounted to RM1,065 billion by the end of June 2018, almost RM350 billion higher than the officially approved estimation of the previous government. This led to many concerns about the country's financial position. KMV model is one of the successful default models initiated to give an early precaution on default risk. However, the application of the KMV model is primarily focusing on the default risk of firms. Therefore, this study attempts to adapt the KMV model to the case of predicting the default risk of sovereign debt. Samples of data from Malaysia and Greece from 2007 to 2016 are utilized to predict the probability of default (PD) in one-year advance and at once to test the model's ability.